Kinetics of mullite formation from kaolinite and boehmite - Heraiz, M; Sahnoune, F; Hrairi, Meftah; Saheb, Nouari; Ouali, A (Taylor & Francis Group, LLC, 2016)
The excellent electrical, thermal and mechanical properties, and good stability of mullite made it a candidate material to produce ceramics for advanced applications such as catalyst supports, filters, optical devices, heat exchangers and electronic packaging. In this work, monolithic mullite was synthesized from kaolinite and boehmite and the kinetics of its formation was investigated using dilamometry. The activation energies for the transformation of kaolinite to metakaolinite, transformation of metakaolinite to spinel, and transformation of the kaolinite-boehmite powder to mullite were evaluated through non-isothermal treatment following the Kissinger and Ozawa equations. The growth morphology parameters were evaluated for the transformation of metakaolinite to spinel, and for the transformation of the spinel to mullite.